Innovation in the promotional mix elements and its impact on ‎the rapid spread of new products An analytical study of the opinions of a sample of beneficiaries display ‎smartphone "Lenovo - Amina Therif; Ilyes Benssassi (Dirassat Journal Economic Issue, 2020)
Innovation has become an important factor to support the marketing communications in leading enterprise, Innovation in this communication element vital will facilitate the delivery of successful new products, and will contribute to the establishment of relations with all parties dealing with this foundation, and enhance its reputation in the long term, as to ensure her success and continue, and achieve a unique competitive advantage, Therefore this research paper seeks to identify and analyze the impact of innovative methods applied in the promotional mix in in order  to accelerate the spread of new products among consumers, by focusing  on the promotional offer submitted recently by "Ooredoo" Foundation for Smartphone "Lenovo", and to achieve these goals have been prepared a questionnaire to collect data from a sample of which there were 61 single individuals, the study reached a number of results, the most important ones: the impact of  the innovation in advertising and personal selling on the rapid spread of this new offer, while the remaining elements of sales promotion and direct marketing did not have an impact on the fast spread of smartphone display "Lenovo" investigator among them. The study recommends the necessity to pay more attention to the content and form, and the credibility of the consumer-oriented advertising messages, as they have a major role in attracting the consumer to the enterprise products, and it speed fast, and orientation promotional campaigns innovative corporate with each category by age, income and educational level, because each of these social variables play an important role in the rapid spread of new products.